Coastal and Small Islands Management: Commitment and Practising in South Sulawesi - Maskun,; Patittingi, Farida; Naswar,; Achmad,; Assidiq, Hasbi (International Journal of Psychosocial Rehabilitation, 2020)
The Provincial Government of South Sulawesi has enacted a regional regulation related to the zoning plan of the Coastal and Small Islands Areas (WP3K) which is the basis for the management of the WP3K spatial plan in South Sulawesi. This paper will analyze the commitment of the Government of South Sulawesi in managing of sustainability of WP3K. This study uses a normative approach to analysis some relevant regulations in order to provide a scientific argumentation for the government to evaluate the existed regulations and to guarantee a fair and sustainable WP3K spatial plan. The results of the study show that although the South Sulawesi region already has regulations related to WP3K, there are still some weaknesses that result in inequality in WP3K space management and threaten the preservation of marine ecosystems in South Sulawesi.